Efficacy and safety of bloodletting therapy for acute herpes zoster: a systematic review and meta-analysis - Wu, Danhui; Jiang, Yanbin; Wu, Qiqi; Jin, Yibo; Wang, Chenda; Guan, Lihua; Shao, Wei (Frontiers in Neurology, 2025)
BackgroundThe high incidence of acute herpes zoster (HZ) and limitations of conventional therapies in pain control necessitate exploration of complementary approaches. Bloodletting therapy (BLT), a traditional intervention with potential analgesic and immunomodulatory effects, has been increasingly applied in China, yet its efficacy remains controversial due to inconsistent clinical evidence.MethodsA systematic search was conducted in databases including PubMed, Embase, the Cochrane Library, MEDLINE, CNKI, the Wan Fang database, the Chinese clinical trial registry, and VIP Chinese Science from inception to June 2025 to identify randomized controlled trials (RCTs) comparing bloodletting therapy vs. pharmacotherapy in acute HZ (≤10 days post-eruption). Primary outcomes included Clinical efficacy rate, Visual Analog Scale (VAS), Skin lesion presentation, Incidence of PHN. Risk of bias was assessed using Cochrane RoB 2.0. Data were pooled via appropriate statistical methods (RevMan 5.4). PROSPERO registration: CRD420251110060.ResultsA total of 16 RCTs involving 1,283 patients were included. Meta-analysis demonstrated that bloodletting therapy significantly improved clinical efficacy versus pharmacotherapy (OR = 4.51, 95%CI [2.89, 7.04], p < 0.00001). Furthermore, BLT achieved superior pain reduction, evidenced by lower VAS scores (MD = -1.57, 95%CI [−1.93, −1.21], p < 0.00001), and accelerated skin healing through shorter crust formation (MD = -1.58 days, 95%CI [−1.79, −1.38], p < 0.00001) and scab detachment times (MD = -2.53 days, 95%CI [−3.82, −1.23], p = 0.0001). Importantly, BLT reduced PHN incidence (OR = 0.23, 95%CI [0.15, 0.35], p < 0.00001). Regarding safety, adverse events were comparable between groups (OR = 0.66, 95%CI [0.31, 1.38], p = 0.26). Subgroup analyses suggested the superiority of fire needle techniques. Sensitivity analyses resolved high heterogeneity in some outcomes.ConclusionBased on existing evidence predominantly, BLT may be associated with superior short-term outcomes in pain relief, skin lesion healing, and PHN prevention for acute herpes zoster compared to pharmacotherapy, and its safety profile appears acceptable. However, these findings must be interpreted with considerable caution due to the high risk of bias in the included studies and significant clinical heterogeneity. Moreover, the generalizability of the results is limited as all trials were conducted within a single region (China). Therefore, international, high-quality RCTs with standardized protocols and longer follow-ups are urgently needed to confirm these potential benefits and establish the long-term efficacy and safety of BLT.